Indicadores da análise técnica no mercado FOREX - SOUZA, Edinei David de (2022)
This project presents as the central theme the study of technical indicators of the Forex market, some models of market trends, enabling the knowledge of mobile media, Relative Strength Index and Bollinger Bands, besides showing a brief history of the national financial market. . This paper will present the main concepts of Technical and Fundamental Analysis for the best results when it comes to investing in the Forex market. This research aims to verify the indicators at the time of decision making, as well as the proportion of another indicator to assist the investor when applying his money. The result was the creation of a new tool that also serves as support for analysis in the foreign exchange market. Lastly a comparison with the suggested indicator (Adapted Moving Average) with the commonly used indicator.